IMPACTS OF NON-PLANE WAVES ON TWO-STATION MEASUREMENTS OF PHASE VELOCITIES - Pedersen H.A. (My University, 2006)
To determine the regional shear wave velocities in the lithosphere it is frequently necessary to use two-station dispersion curves. We investigate the influence of non-plane wave energy on such dispersion curves, and compare them to two other better known sources of error: deviations from great-circle paths and uncorrelated noise. To study the influence of non-plane waves created from distant heterogeneities we create complex wavefields in a laterally homogeneous medium by adding interfering waves to a main plane wave. We then calculate the apparent phase velocity between two seismic stations located 100-400 km apart. Using realistic values for the sources of error, we conclude that the contribution of each is similar for 200-km-long profiles. Our conclusions on non-plane waves are made under the assumption that non-plane energy from distant heterogeneities varies randomly with hypocentre location. If this is correct, then only five to 10 events with different hypocentres are required to obtain a stable dispersion curve with less than 1 per cent error. The influence of uncorrelated noise and non-plane waves diminish for longer profiles, while the errors due to great-circle deviations are independent of profile length and systematically bias the dispersion curve to higher velocities. We recommend the inclusion of some off-profile broad-band stations for surface wave studies on a regional scale, because such supplementary stations make it possible to apply first-order corrections for off great-circle propagation. The strong influence from the different sources of error, combined with our lack of precise knowledge of the nature and amplitude of non-plane energy, implies that the interpretation of two-station measurements should be restricted to major changes in regional earth structure. © 2006 The Author Journal compilation © 2006 RAS.
Keywords: LITHOSPHERE; SEISMIC VELOCITIES; SEISMIC WAVE PROPAGATION; SURFACE WAVES